Improving Ability Of Ognate Base Of Child Through Method Giving Og Duty In Group A Of Bala Keselamat Kenderga Then Lilian Kulawi - Paheru, Meli (Bungamputi, 2014)
ABSTRACT The background of this researchis the problem in group A is the growth of abifity of cognate base of child less maximal. To overcome the problem hence conducted repair of study process with aim to improve the resultof learning one of them growth of smooth motorik. Selected Action alternative that is method giving of duty with assumption to the number of given duty affect at cognateabifity of him. Its device relate at model groove PTK started from reflection planning, observation and execution by have cycle. Group child of A amounting to 20, 9 boys and 11 girls. Coileted data with giving duty, Question and answer observation and documentation hereinafter analysed by descriptive qualitative with percentage technique. Inferential that method giving of duty can inprove ability of cognate base of proven child there is make-ip of ability of base of cycle one to cycle two 45% becoming 82,5% or 37,5%, although there are still which is not yet successes to improve their ability 18,75%.